Pambolus oblongispina Papp, 2000 (Braconidae: Pambolinae), first record in Mexico - Coronado Blanco, Juana María; Ruiz Cancino, Enrique (Instituto de Ecología, A.C., 2013)
Braconidae is one of the insect families with more diversity in the world. Pambolinae is one of the most distinctive subfamilies because the spines present on the propodeum. In this note, Pambolus oblongispina Papp is a new record for Mexico, collected in the State of Tamaulipas. This species was previously known only from Honduras.